OPEN GOVERNMENT PARTNERSHIP: KEY ISSUES IN SEKONDI-TAKORADI - Syed Agung Afandi; Rizki Erdayani; Muslim Afandi (Journal of Contemporary Public Administration, 2025)
Sekondi-Takoradi plays a leading role in the open government campaign in Ghana as it is the only pilot local government program of the Open Government Partnership in the country. The purpose and focus of this study are to analyze the key issues of open government in Sekondi-Takoradi. Qualitative approaches and bibliometric analysis methods were used in this study. The research data were obtained from the official website of the Sekondi-Takoradi government and sourced from the Google Scholar database. The findings of this study indicate that open government in Sekondi-Takoradi is not popular. The dominant issues of open government in Sekondi-Takoradi include development, governance, policy, economy, decentralization, reform, innovation, and SMEs. Meanwhile, current issues include urban economy, leadership, SME resilience, open innovation, open governance, transportation, and sustainable development. These issues highlight the urgency and potential future contributions to open government in Sekondi-Takoradi. Currently, Sekondi-Takoradi is focused on three key commitments: creating climate resilience, building synergies to impact water and sanitation outcomes, and improving responsiveness and efficiency in municipal service delivery through E-Government. These commitments have the potential to create a more open government in Sekondi-Takoradi. The findings of this study serve as recommendations for decision-makers in Sekondi-Takoradi, as well as for all local governments in Ghana and all members of the Open Government Partnership.